2003
DOI: 10.1002/eji.200323564
|View full text |Cite
|
Sign up to set email alerts
|

Thymic epithelial cells provide Wnt signals to developing thymocytes

Abstract: Interactions with thymic stromal cells are known to be critical for the development of T cells from progenitors entering the thymus, yet the molecular mechanisms of stromal cell function remain poorly understood. Accumulating evidence has highlighted the importance of gcatenin-mediated activation of T cell factor (TCF)/lymphoid enhancer factor (LEF) transcription during thymocyte development. As regulation of this signaling pathway is controlled by binding of soluble Wnt proteins to cell surface Frizzled (Fz) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
85
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 32 publications
8
85
0
2
Order By: Relevance
“…Wnt4 has been shown previously to be expressed in fetal TECs, 22,33 but little is known on its potential expression by other thymic stromal components and thymocyte subsets. We now compared Wnt4 mRNA expression by qRT-PCR in different thymic stromal fractions (TECs, endothelial cells, and fibroblasts) as well as thymocytes both in E18.5 fetal thymus and in young adult mice.…”
Section: Wnt4 Is Predominantly Expressed By the Tecsmentioning
confidence: 99%
“…Wnt4 has been shown previously to be expressed in fetal TECs, 22,33 but little is known on its potential expression by other thymic stromal components and thymocyte subsets. We now compared Wnt4 mRNA expression by qRT-PCR in different thymic stromal fractions (TECs, endothelial cells, and fibroblasts) as well as thymocytes both in E18.5 fetal thymus and in young adult mice.…”
Section: Wnt4 Is Predominantly Expressed By the Tecsmentioning
confidence: 99%
“…Numerous Wnt genes are expressed in thymocytes or in thymic epithelial stromal cells ( 22 ), and overexpression of Wnt genes can increase thymocyte proliferation in vitro ( 23 ). Mice defi cient in LEF1/TCF1 are depleted of ␣ ␤ lineage thymocytes, and overexpression of extracellular Wnt inhibitors can partially block ␣ ␤ T cell development in fetal thymic organ cultures (FTOCs) ( 24 -26 ), suggesting that canonical Wnt signaling is essential for normal thymocyte development.…”
Section: Brief Definitive Reportmentioning
confidence: 99%
“…[79][80][81][82] Conversely, Fz receptors are expressed primarily by the thymocytes, but also by stromal cells. 79 79 Recently, our group has shown that mainly DN1-3 thymocytes undergo Wnt signaling.…”
Section: Notch and Wnt Signaling In T-cell Development And T-allmentioning
confidence: 99%
“…Presence of b-catenin mRNA was detected in all thymoycte subsets. 80 Mice with b-catenin deleted in all T cells from DN3 onwards showed impaired T-cell development at the b-selection checkpoint, 90 but mice transplanted with HSCs in which b-catenin had been inducibly deleted, did not show in any thymic defect. 91 As possible explanation, redundancy between b-catenin and its homologue plakoglobin (g-catenin) has been suggested.…”
Section: Notch and Wnt Signaling In T-cell Development And T-allmentioning
confidence: 99%